Development Of Man To Machine (M2M) Ratio Technique In Semiconductor Company - Rohana, Abdullah (2009)
Tough global competition requires every manufacturer to be more creative on ways to reduce every aspect of their operational cost. To remain competitive, manufacturers need to shorten the cycle time in New Product Introduction to capture the market share,reduce manufacturing cost and explore ingenious ways to improve productivity. Labor cost is among the key cost contributors that the manufacturers are focusing on and lean manufacturing is among the strategy taken by many companies to improve their competitive advantage. Labor productivity improvement is all about getting more units out with the same or lesser amount of labor. Before determining the ideal number of people required for the operation, a proper method of defining the current utilization of the labor working on the equipment in the production line is required. Once the current labor utilization is known, only then the ideal utilization of the operator can be accurately determined and recommendations for productivity improvements can be made. Hence, the purpose of this research is to develop a suitable work study technique to measure the labor productivity at the semi-auto back-end semiconductor manufacturing line. This thesis aims to discuss the development of a work study technique called the Man to Machine Ratio (M2M) to determine the present manning utilization and propose ideal man to machine ratio of the back end semiconductor manufacturing processes. M2M technique was derived through the determination of the key factors from the established method of Process Mapping and Multi Machine Chart. In addition, MOST Predetermined Time Standard was used as the method to perform work measurement. To assist in the measurement stage, the M2M template was designed using Microsoft Excel Spreadsheet.Next, five case studies utilizing the Lean Six Sigma DMAIC project management approach were carried out to test the suitability of the M2M method at the back end semiconductor manufacturing line based on a set of key criteria. The case study results showed that the M2M method was able to determine labor utilization and man to machine ratio, provide accurate data and have the flexibility to be used at both manufacturing and non manufacturing processes. Moreover, M2M is easy to develop, maintain and communicate and does not require a high skill set. By employing the M2M method together with DMAIC systematic approach, focus area for productivity improvement could be identified and the back end semiconductor company will be on the right track towards achieving a leaner operation.